Outcome and safety 90 days after combined airway valve treatment of the right upper and middle lobes in patients with severe pulmonary emphysema - Dittrich, A. Susanne; De Pace, Cosimo Carlo; Brock, Judith; Trudzinski, Franziska; Heußel, Claus Peter; Eberhardt, Ralf; Herth, Felix; Kontogianni, Konstantina (Respiratory research, 2025)
In COPD patients with severe right-sided emphysema, complete major and incomplete minor fissure, implantation of one-way valves in both the right upper (RUL) and middle lobes (ML) is a possible approach for endoscopic lung volume reduction. The aim of this retrospective analysis was to evaluate the response to therapy and the complication rate at 90 days (90d-FU) after combined RUL-ML valve implantation.